1998
DOI: 10.1111/1467-9566.00082
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Curriculum of Patient Education for Low Back Pain in General Practice

Abstract: In this article I explore the implicit learning that occurs in and through doctor-patient educational encounters in general practice. Drawing upon a recent study of low back pain, I argue that whilst general practitioners appear to dominate the process of patient education, this process cannot be viewed simply as a repressive social control mechanism. Rather patients voluntarily choose to exert bodily self-controls in the light of patient education, due to their wider association with freedom, health and perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The other study explored GPs' beliefs about education and found that GPs felt there was not enough time within the consultation to deliver it even though they felt it was important. 20 This study found that GPs viewed education as preventive, and that many implicitly blamed patients for their low back pain, if they did not adhere to the educational program offered.…”
Section: Beliefs About Pain Causation and Influences On These Beliefsmentioning
confidence: 81%
See 3 more Smart Citations
“…The other study explored GPs' beliefs about education and found that GPs felt there was not enough time within the consultation to deliver it even though they felt it was important. 20 This study found that GPs viewed education as preventive, and that many implicitly blamed patients for their low back pain, if they did not adhere to the educational program offered.…”
Section: Beliefs About Pain Causation and Influences On These Beliefsmentioning
confidence: 81%
“…For 2 studies, we included several articles from the same study, as they reported different aspects of the study that were all relevant to this review. [18][19][20][21] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also partly due to 'concerns about the inexorable rise in medical care costs' (Bartlett, 1986: 141). The major part of patient education (compared to health education, which is concerned with the asymptomatic individual or population (Skelton, 1998)) seems to concern the practical management of chronic illnesses like diabetes, hypertension and rheumatoid arthritis (RA) and to help patients to help themselves (cf. Bartlett, 1986;Lorig, Konkol and Gonzales, 1987).…”
Section: The School As Metaphormentioning
confidence: 99%